Effect of Different Quantities of Irrigation on Soil Moisture -variation Pattern, Soil Properties and Net Returns of Wheat Crop. - Reddy, D Subbarami; Dakshinamurti, C (Annals of Arid Zone, 2016)
The rates of moisture depletion from the soil with different quantities of irrigation applied, namely 1/2,3/4. 1, 3/2. 2, and 3 times of field capacity levels. were studied in a sandy loam soil of Delhi. The rates of depletion in 3/2,2 and 3 FC treatments were found to be greater till 8 days after irrigation and thereafter almost equal as that in 3/4 FC treatment. Bulk density and dispersion coefficient were found to be minimum in 3/4 FC treatment followed by FC. The values of electrical conductivity, HCO3, Cl. S04, Ca, Mg, Na and K of the soil had increased with increased quantity of irrigation applied from 1/2 FC to 3 FC level. The net income per hectare was found to be maximum with 3/4 PO: level of irrigation followed by I FC fol’ both the wheat varieties studied. Further the results Indicated that growing a wheat crop under rain red conditions of agriculture was found to be more beneficial than under irrigated conditions of giving more than 3/2 FC level of irrigation.